2016
DOI: 10.15537/smj.2016.12.17059
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ awareness and knowledge of adverse drug reactions and pharmacovigilance

Abstract: ObjectivesTo document the knowledge of, attitudes toward, and practices of adverse drug reaction (ADR) reporting and pharmacovigilance systems among healthcare professionals.MethodsThis descriptive cross-sectional study was conducted using a questionnaire. This study took place at King Fahd Hospital of the University (KFHU), Khobar, Kingdom of Saudi Arabia, between April 2015 and April 2016. Healthcare professionals, including physicians, pharmacists, pharmacy technicians, and nurses, were considered eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 11 publications
3
74
4
Order By: Relevance
“…However, some studies show statistically significant differences between the healthcare professionals. Among studies that included other healthcare professionals, pharmacists were more likely to see an ADE and more likely to be aware about the existence of pharmacovigilance centres and reporting forms compared to doctors and nurses . No difference in the mean knowledge/attitudes was found between the three healthcare professional in some studies or reporting rate .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, some studies show statistically significant differences between the healthcare professionals. Among studies that included other healthcare professionals, pharmacists were more likely to see an ADE and more likely to be aware about the existence of pharmacovigilance centres and reporting forms compared to doctors and nurses . No difference in the mean knowledge/attitudes was found between the three healthcare professional in some studies or reporting rate .…”
Section: Resultsmentioning
confidence: 89%
“…Among studies that included other healthcare professionals, pharmacists were more likely to see an ADE and more likely to be aware about the existence of pharmacovigilance centres and reporting forms compared to doctors and nurses. [25,28,42,46,[67][68][69][70] No difference in the mean knowledge/attitudes was found between the three healthcare professional in some studies [27,33,71,72] or reporting rate. [67] However, other studies found that pharmacists have better knowledge of ADEs than nurses [50,73] and pharmacists have better mean knowledge score compared to physicians.…”
Section: Reporting Of Ades By Pharmacists Compared To Other Hcpsmentioning
confidence: 99%
“…[16] Likewise in another study at Saudi 88.8% had never reported, submitted, or identified any ADR reports. [17] According to a systematic review [18] in 2016 based on 28 studies three-quarters (74.5%, 95% confidence interval 67.9-81.9; P < 0.001) of the sample declared that they never reported any ADR to PV centers.…”
Section: Discussionmentioning
confidence: 99%
“…Drug delivery enhances the efficacy of drugs through controlled release by considering the factors like carrier system, route of administration and target of drug action. Drug delivery system improves patient compliance, therapeutic index and bioavailability [1].…”
Section: Introductionmentioning
confidence: 99%